2022
DOI: 10.3390/ijerph191912467
|View full text |Cite
|
Sign up to set email alerts
|

Building Capacity for Community-Academia Research Partnerships by Establishing a Physical Infrastructure for Community Engagement: Morgan CARES

Abstract: Research partnerships between universities and communities following the principles of community-based participatory research (CBPR) have the potential to eliminate cycles of health disparities. The purpose of this article is to describe the process of establishing a community-campus network with a distinct mission and vision of developing trusting and successful research partnerships that are sustained and effective. In 2019, Morgan CARES was established to facilitate community engagement by founding a commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
(26 reference statements)
1
2
0
Order By: Relevance
“…[ 42 , 52 , 53 ]. These findings align with existing literature on community-based health interventions targeting underserved populations [ 28 , 29 ]. A study by Kangovi and colleagues (2014) observed significant improvements in chronic disease control and mental health outcomes with a community health worker intervention implemented in a low-income urban population and [ 54 ].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…[ 42 , 52 , 53 ]. These findings align with existing literature on community-based health interventions targeting underserved populations [ 28 , 29 ]. A study by Kangovi and colleagues (2014) observed significant improvements in chronic disease control and mental health outcomes with a community health worker intervention implemented in a low-income urban population and [ 54 ].…”
Section: Discussionsupporting
confidence: 88%
“…[42,52,53]. These findings align with existing literature on community-based health interventions targeting underserved populations [28,29].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Studies exploring the benefits of a community of practice among peers acknowledge positive reinforcement and reassurance [15,16] while refraining from criticism or pointing out weaknesses [17]. Coto [18] gave a detailed account of the practices of digital communities of practice, CoPs, among faculty members in Higher education.…”
Section: Features and Benefits Of Vcopmentioning
confidence: 99%